BAKTI SOSIAL BERSIH-BERSIH TELINGA DI BANJAR JAGATAMU, DESA MELILING, KERAMBITAN – TABANAN OLEH DOSEN FAKULTAS KEDOKTERAN UNIVERSITAS MAHASARASWATI DENPASAR - Ida Ayu Mirah Agung; I Gusti Ayu Prema Yani Sidemen; Anak Agung Istri Aiswarya Novitrianti (Bajang Institute, 2025)
Ear and hearing health is an important thing that needs special attention. Disorders of the ear and hearing can cause several disorders, such as ear infections, balance problems, and even permanent hearing loss. Good ear and hearing health can be achieved by adopting healthy habits and attitudes based on good knowledge in ear and hearing health. One of the causes of hearing loss that often occurs is cerumen block/cerumen obsturans/cerumen impaction. As a form of community service and realizing the main goal of the WHO Sound Hearing 2030 program, lecturers from the Faculty of Medicine, Mahasaraswati University, Denpasar, held a health service in Banjar Jagatamu, Meliling Village, Kerambitan - Tabanan, namely Bersih-Bersih Telinga (BBT) to reduce the incidence of deafness due to cerumen. In addition to cleaning the ears, the health service activities were also filled with consultations regarding community complaints in the field of ears, nose, and throat